Learning Pathway Recommendation based on a Pedagogical Ontology and its Implementation in Moodle - Henning, Peter A; Forstner, Alexandra; Heberle, Florian; Swertz, Christian; Schmölz, Alexander; Barberi, Alessandro; Verdú, Elena; Regueras, Luisa M.; Verdú, María J; de Castro, Juan-Pablo; Burgos, Daniel; De la Fuente-Valentin, Luis; et al. (Lecture Notes in Informatics, 2023)
When learners may select among different alternatives, or are guided to do so by an adaptive learning environment (ALE), it is generally meaningful to discuss the concept of different learning pathways. Pedagogically, these learning pathways may either be defined macroscopically, e.g. in terms of desired learning outcomes or competencies, or microscopically in terms of a didactical model for individual knowledge objects. In this contribution we consider such learning pathways from a pedagogical point of view and then establish a mathematical model for their traversal by a learner and for the analysis of his behavior. This model is implemented in a novel ALE provided by the EU FP7 project INTUITEL, introduced in its Moodle version as concrete example.
Keywords: learning pathway; pedagogical ontology; Moodle; Scopus(2)